Penyelesaian piutang tak tertagih pada primer koperasi purnawirawan abri (primkoppabri) kabupaten blitar - Endah Masrunik; Arif Wahyudi; dewi Frenti (JURNAL EKUIVALENSI, 2020)
Giving credit to the cooperative always has a risk, for that the cooperative must try and plan carefully so that the risk of the emergence of problem loans can be reduced. The purpose of this study is to find out the development of non-performing loans at the Blitar Regency Retirement Cooperative Primer (PRIMKOPPABRI) in Blitar Regency, to know the impact caused by non-performing loans at the Purnawirawan ABRI Cooperative Primer (PRIMKOPPABRI) in Blitar Regency, and to Know the Problem Settlement of the Purnawirawan Cooperative Primary Primer. ABRI (PRIMKOPPABRI) Blitar Regency. The method used in this research is qualitative method. The results of the study show that the Primary Retirement Cooperative of the Indonesian Armed Forces (PRIMKOPPABRI) Blitar Regency experiences problem loans, and the impact on cooperatives is to disrupt the performance of cooperative management, increased costs incurred, bank profits are reduced, and cooperative capital is threatened undeveloped, while the impact on customers is the image the customer gets worse, and the loss of variety may be the next opportunity. Efforts by cooperatives to resolve problem loans are through alternative rescheduling, reconditioning, and restructuring.